When and Why Do Venture-Capital-Backed Companies Obtain Venture Lending?. (15th June 2017) - Tykvová, Tereza
Abstract : I model the decision of an informed early-stage venture capital (VC) investor that considers involving an uninformed VC or venture lending (VL) investor to finance the late stage. Early-stage VC investors that own high-quality value companies tend to signal their quality and they frequently turn to VL investors. Early-stage VC investors prefer VC if the proportion of high-quality companies in the population is high, if their companies have a high upside potential, if they can benefit from the value that late-stage VC investors add, or if uncertainty is high. I find empirical evidence consistent with these predictions.